HUBUNGAN STATUS GIZI DAN ASUPAN BESI DAN SENG TERHADAP FUNGSI MOTORIK ANAK USIA 2-5 TAHUN - ARDIARIA, MARTHA; NURYANTO, NURYANTO (Universitas Diponegoro, 2014)
Background: Motoric development is one of crucial step throughout the life cycle. Any disturbances in this step leads to growth and development abnormality. Variables controls the child?s motoric development are nutritional status, iron and zinc intake. This study aims to assess the correlation of nutritional status, iron and zinc intake with the motoric function among children. Method: This study is a part of the bigger study titled The Effect of Zink Supplementation and Vitamin A to Immune Response and Morbidity among Preschool-aged children in Semarang. Study design iscross sectionalwith purposive sampling. Data depicted anthropometric nutritional status, iron and zinc intake through Food Frequency Quantifiedand motoric function score based on the standard of Ministry of Health. Data analysis used the Pearson test and Rank Spearmanfor normality. Result:The lowest and highest motoric function was 11 and 100% respectively. The average nutritional status showed in Z score was?1,60 ± 1,10 (mild malnutrition), Height/Age index -1,86 ± 0,97 (mild malnutrition) andWeight/Height -0,60 ± 1,09 (normal). There was no correlation between nutritional status and motoric function. Iron and zinc adequacy were below the standard, 79,1% and 94,5% respectively. There was a positive correlation between iron intake and motoric function (r: 0,309; p: 0,003) and so were the zinc intake (r: 0,284; p: 0,006). Conclusion:There is a correlation between the iron, zinc intake and motoric function among children Key word:Nutritional satus, iron intake, zinc intake, child?s motoric function